Accuracy of three-dimensionally printed interim removable partial dentures: An in vitro study - Sumin Kim; Ha Eun Choi; Kyung Chul Oh (Heliyon)
Accurately replicating the pre-planned internal relief between the denture base of interim removable partial dentures (RPDs) and the underlying soft tissues in edentulous areas, as designed in the computer-aided design (CAD) phase, is crucial. This study aimed to evaluate the accuracy of three-dimensionally (3D) printed denture bases for interim RPDs by comparing them with their corresponding CAD files to ensure adequate space and uniform thickness for soft denture liners. Ten 3D-printed mandibular interim RPDs were fabricated with internal reliefs of 1 mm and 2 mm. Reference points were marked on each RPD, and they were divided into two groups based on the presence (group TS) or absence (group FE) of the most distal tooth. The silicone replica technique was used to compare differences based on the presence of the most distal tooth and measurement locations for each internal relief condition. Data were analyzed using two-way analysis of variance and post-hoc tests. No significant differences were observed in measurement locations for either the 1-mm or 2-mm internal relief conditions. In the 1-mm internal relief condition, there were no significant differences based on the presence of the most distal tooth. However, in the 2-mm internal relief condition, group TS showed significantly higher accuracy compared to group FE. This suggests that a 1-mm internal relief RPD may offer more predictable outcomes regardless of the presence of the most distal tooth.